The non-impairment of pollination and fertilization in the abscission of chilli (Capsicum annuum L. Var. Kulai) flowers under high temperature and humid conditions - Usman, Inuwa Shehu; Mamat, Awang Soh; Syed Zain Mohd, Syed Hasan; Hassan, Siti Aishah; Anuar, Abd.Rahim (1999)
Pollination and fertilization in abscising chilli flowers were studied under glasshouse and field (pot plants planted in the field) conditions of high temperature and high humidity. Pollen viability, pollen tube growth and fertilization in abscising chilli flowers were similar under both conditions. The number of seeds per fruit and percent seed germination were also similar. Findings indicate that abscission of chilli flowers in Kulai variety under high temperature and humid conditions proceed independently of the processes of pollination and fertilization.